Three mononuclear octahedral cobalt(III) complexes with salicylaldimine Schiff bases: Synthesis, characterization, phenoxazinone synthase mimicking activity and DFT study on supramolecular interactions. (7th July 2016) - Ghosh, Kousik; Roy, Sumit; Ghosh, Anindya; Banerjee, Abhisek; Bauzá, Antonio; Frontera, Antonio; Chattopadhyay, Shouvik
Graphical abstract: Three mononuclear octahedral facial cobalt(III) complexes have been synthesized and characterized. The structures have been confirmed by single crystal X-ray analysis. Supramolecular interactions in solid state in them have been analyzed with DFT study. Two complexes show phenoxazinone synthase mimicking activity. Abstract: Three mononuclear facial cobalt(III) complexes, [Co(L)2 ]ClO4 (1 ), [Co(L)(bzan)(N3 )] (2 ) and [Co(L)(bzan)(NCS)] (3 ), {HL = 2-(3-(dimethylamino)propyliminomethyl)-6-ethoxyphenol and Hbzan = 1-benzoylacetone} were prepared and characterized by elemental and spectral analysis. X-ray crystal structure determination confirmed their structures. Extended supra-molecular assemblies were generated in all three complexes through weak noncovalent interactions. Density functional theory (DFT) calculations were employed to understand and estimate the contribution of each interaction in the formation of the assembly using several theoretical models. Bader's theory of "atoms in molecules" (AIM) was also used to further describe the long range interactions and its role to stabilize different molecular assemblies. Complexes2 and3 were found to be efficient catalysts to perform the aerial oxidation of 2-aminophenol to 2-aminophenoxazine-3-one and therefore could be used as functional models for copper(II) containing enzyme, phenoxazinone synthase.